2021
DOI: 10.1542/peds.2020-001230
|View full text |Cite
|
Sign up to set email alerts
|

Extremely Low Birth Weight and Accelerated Biological Aging

Abstract: BACKGROUND AND OBJECTIVES: Extremely low birth weight (ELBW) (,1000 g) survivors are exposed to elevated levels of physiologic stress during their lives and may be susceptible to accelerated aging. Using the oldest known longitudinally followed cohort of ELBW survivors, we compared biological aging in this group using an epigenetic clock to a sample of matched normal birth weight (NBW) (.2500 g) control participants.METHODS: Buccal cells were collected from 45 ELBW survivors and 49 NBW control participants at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 60 publications
0
16
0
1
Order By: Relevance
“…In contrast, Phang et al found that neither birth weight nor body fatness is associated with epigenetic age acceleration in newborns [ 28 ••]. In a small study, 30–35-year-old males who had been born with extremely low birth weight had accelerated epigenetic aging compared to their peers born with normal birth weight [ 37 ]. Taken together, these associations suggest links between maternal–fetal wellbeing and offspring epigenetic aging, although the finer detail of these links requires further description.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, Phang et al found that neither birth weight nor body fatness is associated with epigenetic age acceleration in newborns [ 28 ••]. In a small study, 30–35-year-old males who had been born with extremely low birth weight had accelerated epigenetic aging compared to their peers born with normal birth weight [ 37 ]. Taken together, these associations suggest links between maternal–fetal wellbeing and offspring epigenetic aging, although the finer detail of these links requires further description.…”
Section: Resultsmentioning
confidence: 99%
“…Such risk factors include high, low, or extremely low birth weight [ 40 , 41 , 42 ] and the formation of aberrant neural circuits under the influence of genetic and/or environmental factors. Given the increased rates and early emergence of chronic illnesses observed in the individuals born with extremely low birth weight, the latter may confer a premature aging phenotype characterized by accelerated cellular senescence and the development of diseases typically associated with old age [ 133 ]. The mechanisms and potential substrates of these lasting effects are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Such risk factors include high, low or extremely low birth weight [40][41][42], and the formation of aberrant neural circuits under the influence of genetic and/or environmental factors. Given the increased rates and early emergence of chronic illnesses observed in the individuals born with extremely low birth weight, the latter may confer a premature-aging phenotype characterized by accelerated cellular senescence and the development of diseases typically associated old age [136] . The mechanisms and potential substrates of these lasting effects are yet to be elucidated.…”
Section: Discussionmentioning
confidence: 99%